2001
DOI: 10.1079/phn2001148
|View full text |Cite
|
Sign up to set email alerts
|

A review of ethnicity, health and nutrition-related diseases in relation to migration in the United Kingdom

Abstract: Objectives:To identify lessons from and gaps in research on diet-disease links among former migrants in the United Kingdom (UK).Results:Migrant status and self-identified ethnicity do not match so these terms mask differences in social, nutritional and health status within and between population groups. Some former migrants differ in causes of death from the general population, e.g.: fewer coronary heart disease deaths among Caribbean-born; fewer cancer deaths among Caribbean, South Asian- and East African-bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 55 publications
2
75
0
5
Order By: Relevance
“…Previous studies reported that women and older age cohorts consume fruit and vegetables more often than men and younger age cohorts; and that participants with a higher level of education tend to consume more fruit and vegetables than those with a low level of education (15,16,25,40,41) . Generally, our findings correspond to the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that women and older age cohorts consume fruit and vegetables more often than men and younger age cohorts; and that participants with a higher level of education tend to consume more fruit and vegetables than those with a low level of education (15,16,25,40,41) . Generally, our findings correspond to the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature on migration and health suggests that cultural patterns shape physical activity, body images, dietary intake and food preferences (18)(19)(20)(21)(22)(23)(24) . However, the evidence on dietary patterns is mixed (25) . While some studies report that migrant status is associated with a low daily intake of fruit and vegetables or adverse dietary patterns (26,27) , others report that migrant status is associated with a higher daily intake or beneficial dietary patterns compared with the native population of the host country (28)(29)(30)(31)(32) .…”
mentioning
confidence: 99%
“…However, individuals within and between ethnic groups differ in their regional distribution of excess weight, hence BMI is confounded by variability in physique and remains a relatively crude index of risk. For example, Asians are now known to have both greater disease risk [24][25][26] and greater body fatness 27 than Europeans for any given BMI level, which has led to proposals for ethnic-specific BMI cutoffs to identify overweight and obesity. 13 In our own analyses, population differences in BMI did not match those in body shape.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some studies present mixed evidence, i.e. they find that health risks [29] [30] and health outcomes [31]- [37] are unevenly distributed among immigrant groups. The different results can be largely attributed to the specific immigrant group(s) under study as well as to the context (host country) in which immigration took place.…”
Section: Introductionmentioning
confidence: 99%